Policies and Responsibilities of Government Officials during the Covid-19: The Problem of Interpreting the Phrase of Good Faith in Law Number 2 of 2020 - Darsinah, Darsinah; Hasyim, Achmad Dardiri; Mulyo, Mufrod Teguh (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2022)
Abstract: Article 27 Paragraph (2) Law Number 2 of 2020 introduces the term "good faith" which forms the basis for the policy of non-prosecution of government officials either criminally or civilly. The good faith phrase has led to public polemics and debates. This article aims to describe the position of Law Number 2 of 2020 as well as the meaning and the concept of "good faith" as found in Law No. 2 of 2020 based on the Civil Code. This research utilizes the library method. The research results show that: first, Law Number 2 of 2020 is an adequate legal instrument to provide a strong foundation for the government and related institutions to make certain necessary policies and measures during the Covid-19. Second, the good faith phrase as found in Law No. 2 of 2020 can be interpreted and implemented through 4 (four) indicators, namely: (1) there is business; (2) legal guarantees through regulations that are a win-win solution; (3) implementation of regulations that are appropriate and run optimally; and (4) cooperation between all parties. Abstrak: Pasal 27 Ayat (2) Undang-undang Nomor 2 Tahun 2020 menyebut kata “iktikad baik” yang menjadi dasar kebijakan pejabat pemerintah tidak dapat dituntut secara pidana maupun perdata. Frase iktikad baik tersebut sempat menimbulkan polemik dan perdebatan di kalangan masyarakat. Artikel ini bertujuan mendeskripsikan kedudukan Undang-undang Nomor 2 Tahun 2020 dan sekaligus makna dan konsep “iktikad baik” yang ada dalam undang-undang tersebut berdasar Civil Code. Penelitian ini menggunakan metode kepustakaan. Hasil penelitian menunjukkan bahwa: pertama, UU No. 2 Tahun 2020 merupakan perangkat hukum yang memadai untuk memberikan landasan yang kuat bagi pemerintah dan lembaga-lembaga terkait untuk pengambilan kebijakan dan langkah-langkah tertentu yang diperlukan di masa Covid-19. Kedua, frase “iktikad baik” yang ada dalam UU No. 2 Tahun 2020 dapat diinterpretasikan dan diterapkan melalui 4 (empat) indikator, yaitu: (1) adanya usaha; (2) jaminan hukum melalui regulasi yang win-win solution; (3) implementasi regulasi yang tepat dan berjalan maksimal; dan (4) adanya kerja sama antara semua pihak.